What remains [videorecording (DVD)] - Scoggins, Nathan; Scoggins, Nathan; Williams, Cress, 1970-; Lutz, Kellan, 1985-; Heche, Anne; Savante, Stelio, 1970- (Gravitas Ventures, 2023)
A small-town pastor reckons with an act of forgiveness while a sheriff investigates a murder that may be related.